2018
DOI: 10.1371/journal.pone.0200075
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cardiovascular risk factors in adolescents from a middle-income country: Prevalence and associated factors

Abstract: Multiple cardiovascular risk factors are directly related to the severity of atherosclerosis, even in children and adolescents. In this context accurate assessment of risk factors at the individual level play a decisive role in cardiovascular disease (CVD) prevention. The objective of this study was to estimate the prevalence of cardiovascular risk factors, the frequency of their coexistence in individuals, and identify possible determinants associated with this coexistence in Brazilian adolescents. A cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
3
12
0
1
Order By: Relevance
“…One of the reasons for smoking is also the weight reduction, and smoking and drinking are interdependent in the university lifestyle. Since modifiable lifestyle components are clustering in adolescents, interdependency should be investigated in the longitudinal or multivariate study (26). Because obesity is associated with systemic vascular and cardiac damage (27)(28)(29)(30), lifestyle modification is important for the unhealthy university students.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for smoking is also the weight reduction, and smoking and drinking are interdependent in the university lifestyle. Since modifiable lifestyle components are clustering in adolescents, interdependency should be investigated in the longitudinal or multivariate study (26). Because obesity is associated with systemic vascular and cardiac damage (27)(28)(29)(30), lifestyle modification is important for the unhealthy university students.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 83% of adolescents accumulated two, or more, non-communicable diseases (NCD)-risk factors. Jardim et al (2018) [32] have analyzed 1,170 students from the Brazilian Midwestern region and found that most of them presented at least two risk factors (68.9%) and that more than 10% of them presented more than four risk factors for NCD. According to Nunes et al (2016) [33], 9 out of 10 adolescents from Southern Brazil presented two, or more, risk factors for NCD.…”
Section: Plos Onementioning
confidence: 99%
“…Em adolescentes de 10 a 12 anos, prevalência mais elevada de HA entre meninas (11,76% vs 4,76%), está de acordo com estudos brasileiros, que mostraram frequências mais altas nas meninas 22,25 e em desacordo com estudos que mostraram prevalências mais altas nos meninos [26][27][28][29] . Portanto, as meninas apresentaram maiores prevalências de HA independente da faixa etária.…”
Section: Métodounclassified